Association between Presence of RmpA, MrkA and MrkD Genes and Antibiotic Resistance in Clinical Klebsiella pneumoniae Iso-lates from Hospitals in Tehran, Iran - Ronak Bakhtiari; Ali Javadi; Malihe Aminzadeh; Ebrahim Molaee-Aghaee; Zahra Shaffaghat (Tehran University of Medical Sciences, 2021)
Background: Klebsiella pneumoniae is an opportunistic pathogen causing nosocomial infection in human. This study aimed to investigate the relationship between the presence of genes involved in biofilm formation in K. pneumoniae isolated from patients and the presence of antibiotic resistance genes. Methods: Biochemical tests were used for the identification of K. pneumonia isolated from urine samples referred to hospitals in Tehran, Iran, from Sep 2018 to Jan 2020. The antibiotic resistance pattern was performed and biofilm formation was assessed phenotypically. Finally, β-lactamase genes and adhesion genes were detected by the PCR method. Results: We collected 457 K. pneumoniae isolates from hospitals in Tehran, Iran. 110 isolates were resistant to ‎imipenem. Fifty isolates were positive for metallo-β-lactamases that thirty-nine isolates (35.45%) has blaKPC gene, 18 isolates (16.36%) had blaVIM-‎‎1 gene and 9 isolates (8.18%) had blaIMP-1 gene‎ detected by PCR. Sixty isolates (54.54%) had strong biofilm, 35 isolates (31.81%) had moderate ‎biofilm and 15 isolates (13.63%) had weak biofilm. ‎ The presence of adhesion genes in K. pneumoniae isolates significantly ‎correlated with resistance genes (P<0.001). Conclusion: It is clear antibacterial resistance has been significant association with biofilm formation in K. pneumoniae isolates. Therefore, understanding resistance pattern and mechanisms leading to biofilm formation can facilitate efficient treatment of infections caused by K. pneumoniae.